Implementasi Metode Multi Objective Optimization on the Basis of Ratio Analysis (MOORA) dalam Pendukung Keputusan Penentuan Calon Penerima Bantuan Langsung Tunai Dana Desa (BLT) di Desa Oabikase - Tas'au, Emilia; Widiastuti, Tiwuk; Polly, Yulianto T (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Direct Cash Assistance for Village Fund (BLT-DD) is a program of the Indonesian government aimed at helping underprivileged communities at the village level. In its implementation, the selection process of potential recipients of BLT-DD in Oabikase Village often faces obstacles, such as subjectivity in decision-making and limited resources in data processing. This can lead to inaccuracies in targeting the assistance distribution. Therefore, a system is needed to help village officials determine the recipients of BLT-DD more objectively, transparently, and efficiently. This study aims to build a Decision Support System (DSS) using the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method in the selection process of potential recipients of BLT-DD in Oabikase Village. The MOORA method is used because it is capable of processing data based on established criteria and providing rankings according to the weight of each criterion, resulting in more accurate and fair decisions. This system is created to assist village governments in managing data for potential recipients and to reduce subjectivity in the selection process. User Acceptance Testing (UAT) showed satisfactory results with a total score of 90.71%. UAT also recorded that the system has functionality at 93.33%, usability at 92.50%, and compliance at 83.33%, and the Black Box Testing results showed that 54 features are functioning well. This indicates that the system is well-received by users and is ready for implementation. With this system, it is hoped that village government officials can improve service quality and strengthen public trust.